INFLUENCE OF CS, LEVERAGE, EVA, ROI, AND EPS ON STOCK RETURNS IN THE FOOD AND BEVERAGE INDUSTRY - Willy Sitanggang; Yohana Napitupulu; Ruth Handita Damanik (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Background : This study aims to analyze the effect of firm size, leverage, economic value added, return on investment, and earnings per share on stock returns. The data used is secondary data in the form of financial reports of manufacturing companies in the food and beverage sector that are listed on the Indonesia Stock Exchange (IDX) from 2017-2020. Method : The sample was selected using a purposive sampling method, namely sampling based on predetermined criteria and population characteristics in order to generate data. To analyze the data, this study used multiple linear regression and then tested the hypothesis with the t-test (partially) and the F-test (simultaneously) with a significance level of 0.05. Result: The results of this study indicate that simultaneously Company Size, Leverage, Economic Value Added (EVA), Return On Investment (ROI), and Earning Per Share (EPS) have an effect on Stock Return. However, partially the size of the company has an effect on your stock return in the company, while Leverage, Economic Value Added (EVA), Return On Investment (ROI), and Earning Per Share (EPS) have no effect on your stock return on food and beverage companies on the Stock Exchange. Indonesia (IDX) for the period 2017-2020. Conclusion : 6)       All independent variables, namely company size, leverage, EVA, ROI, EPS, are able to influence stock returns simultaneously or can be seen from the Adjusted R-Square of 13.5%, the remaining 86.5% is explained by variables or factors other